Temporal Unpredictability and Probabilistic Uncertainty Induced Anxiety in the Times of COVID-19 Pandemic - Jayaram, Saravanan; Krishnamurthy, Praveen Thaggikuppe; Selvaraj, Divakar; Nemani, Sri Vyshnavi; Rymbai, Emdormi; Sugumar, Deepa; Bhat, Anusha Shreenidhi; Joshi, Meghana; Kumar, Vishnu (Indian Journal of Pharmaceutical Education and Research, 2022)
Human beings prefer a predictable and certain environment over an unpredictable and uncertain environment. No one predicted the coronavirus pandemic and it is not certain when the pandemic will come to an end. Pandemics not only affect the physical health but also the mental health of the public. An increase in anxiety and suicide rates has been reported during the previous pandemics and the same trend is also being observed in this current pandemic as well. Pandemics inevitably result in unpredictable and uncertain environments. Many studies have proven that unpredictability and uncertainty increase the levels of stress and anxiety in animals and humans. Coronavirus pandemic has caused many unpredictable and uncertain events resulting in increased confusion, frustration, stress and anxiety among the public. For instance, the institution of lockdowns was unpredictable and it was uncertain when the lockdowns will be unlocked. Similarly, events that unfolded around the initial touting of chloroquine and hydroxychloroquine as a possible therapeutic agent and later lack of evidence in support of these drugs resulted in extreme confusion and frustration. The uncertainty around if a vaccine for coronavirus will be developed and when it will become available for public use has also caused stress and anxiety. Current studies indicate that coronavirus is not just a respiratory virus but it also affects the kidneys, brain, heart and blood vessels. This unpredictable nature of the virus has caused further confusion and frustration. These unpredictable and uncertain events around the current pandemic might have increased the levels of stress and anxiety among the public.
Keywords: Coronavirus; Pandemic; Unpredictability; Uncertainty; Stress; Anxiety; Suicide